Whon won the Olympics? - Seiler, S. (Sportscience, 2010)
The list of sports in the Winter Olympics has expanded dramatically in recent years, resulting in more medals for nations specializing in winter sports. Canada has emerged as a major Winter Olympic power and is a medal contender in virtually all sports. Smaller winter nations like Norway win most of their medals in a few disciplines, do not have the facilities or resources to develop international contenders in all the winter Olympic sports, and seem to be falling behind in the total medal race. The Winter Olympics have responded to television audiences by introducing exciting events like snowboarding, ski cross, and short track speed skating. No country has profited more from this revamping of the Winter Olympic program than the United States, which won almost half of its record number of medals in these non-traditional events. The Olympic Games as a spectator event depend on their TV friendliness, which in turn influences the choice of events that are added to the Olympic schedule. More speed, bigger tricks, and more head to head racing instead of racing against a clock are hallmarks of this evolution in new and traditional winter Olympic sports. The challenge for Olympic federations and research institutions is to adapt and embrace this evolution as they contribute to enhancing the performances of their athletes.